Measurement of the inclusive nu(mu) charged current cross section on carbon in the near detector of the T2K experiment - Abe, K; Abgrall, N; Aihara, H; Akiri, T; Albert, J; Andreopoulos, C; Aoki, S; Ariga, A; Ariga, T; Assylbekov, S; Autiero, D; Barbi, M; et al. (2013)
T2K has performed the first measurement of νμ inclusive charged current interactions on carbon at neutrino energies of ∼1 GeV where the measurement is reported as a flux-averaged double differential cross section in muon momentum and angle. The flux is predicted by the beam Monte Carlo and external data, including the results from the NA61/SHINE experiment. The data used for this measurement were taken in 2010 and 2011, with a total of 10.8×1019 protons-on-target. The analysis is performed on 4485 inclusive charged current interaction candidates selected in the most upstream fine-grained scintillator detector of the near detector. The flux-averaged total cross section is σCC=(6.91±0.13(stat)±0.84(syst) )×10-39 cm2nucleon for a mean neutrino energy of 0.85 GeV. © 2013 American Physical Society.